2000
DOI: 10.1097/00004872-200018070-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral magnesium supplementation on blood pressure, platelet aggregation and calcium handling in deoxycorticosterone acetate induced hypertension in rats

Abstract: Magnesium supplementation prevents blood pressure elevation in DOCA hypertensive rats. These effects are associated with inhibition of platelet calcium uptake and decreased intracellular free calcium concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 22 publications
4
16
0
3
Order By: Relevance
“…First, the early and persistent reduction in PBMC [Mg 2ϩ ] i that accompanies ALDOST was attenuated by a Mg 2ϩ -supplemented diet and NAC but not by CCB. As we and others have previously reported, 10 14,20,21 and with mineralocorticoid administration in humans. 22 weeks.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…First, the early and persistent reduction in PBMC [Mg 2ϩ ] i that accompanies ALDOST was attenuated by a Mg 2ϩ -supplemented diet and NAC but not by CCB. As we and others have previously reported, 10 14,20,21 and with mineralocorticoid administration in humans. 22 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…10 have been reported in rodent and human platelets during chronic mineralocorticoid excess (inappropriate for dietary Na ϩ intake) and in rodent neutrophils in response to dietary Mg 2ϩ deficiency. 14,22,28 The proinflammatory phenotype seen with dietary Mg 2ϩ deficiency is prevented when such a diet is simultaneously made Ca 2ϩ -deficient. 23 A Mg 2ϩ -supplemented diet has been reported to attenuate endothelin-1 production by heart, aorta, and kidneys in rats receiving DOC/salt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 It has been demonstrated that magnesium supplementation attenuates blood pressure increases in various models of hypertension, including the stroke-prone spontaneously hypertensive rat, 21 angiotensin II-induced hypertension, 22 and mineralocorticoid salt hypertension. 3,23,24 Although the effects of magnesium on blood pressure seem to be more rapid and pronounced in disease states such as hypertension, 21 our data indicate that chronic magnesium deficiency also influences blood pressure in normotensive animals.…”
Section: Discussionmentioning
confidence: 66%
“…Sin embargo otros autores refi eren que se reducen las cifras de PA, y que también disminuyen la incidencia de ACV 77,78 . En el mismo sentido, junto a la ingesta de vitamina D, podrían reducir la PA y también la frecuencia cardíaca en pacientes año-sos 79 . Podríamos concluir, en cuanto a las sales de calcio, que para confi rmar un potencial efecto protector son necesarias más investigaciones, ya que la evidencia actual no es sufi ciente para recomendar su uso en el tratamiento de la hipertensión arterial.…”
Section: ¿Cómo Infl Uyen Los Otros Minerales Presentes En Las Aguas Nunclassified